2021
DOI: 10.3390/jmse9060569
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Maneuverability of Fishing Vessel Considering Hull-Form Characteristics

Abstract: Fishing vessels with a length (LBP) of less than 100 m are generally not required to comply with the mandatory IMO Ship Maneuverability Standards. Therefore, an analytical method using empirical formula is preferred rather than a model test, which consumes a lot of time and monetary resources in estimating the maneuverability at the design stage. However, most empirical formulas have been derived from the model test results of merchant ships, and in the process, estimation errors may occur when hull-form param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In the process of estimating the maneuverability of a vessel using empirical formulas, the main specifications and hull form characteristics of the vessel may affect the estimation accuracy, as described in Section 2.2. The authors of this paper have already confirmed in a previous study that the hull form of fishing vessels has unique characteristics that are somewhat different from those of the merchant ships' hull form [8,10]. To estimate the maneuverability of the fishing vessels' hull form more accurately, a modified empirical formula was derived from Kijima et al (1990) original empirical formula.…”
Section: Modified Empirical Formulamentioning
confidence: 72%
See 4 more Smart Citations
“…In the process of estimating the maneuverability of a vessel using empirical formulas, the main specifications and hull form characteristics of the vessel may affect the estimation accuracy, as described in Section 2.2. The authors of this paper have already confirmed in a previous study that the hull form of fishing vessels has unique characteristics that are somewhat different from those of the merchant ships' hull form [8,10]. To estimate the maneuverability of the fishing vessels' hull form more accurately, a modified empirical formula was derived from Kijima et al (1990) original empirical formula.…”
Section: Modified Empirical Formulamentioning
confidence: 72%
“…However, since fishing vessels relied on the empirical formula rather than model tests, there was a limitation for collecting model test results for fishing vessels to derive an empirical formula tailored to fishing vessels. In light of this, the authors previously conducted a study to modify the empirical formula originally developed for merchant ships' hull form so that it could be applied to fishing-type vessels as well [5][6][7][8]. The model empirical formula used for this study was the one proposed by Kijima et al (1990).…”
Section: Kijima Et Al (1990) Empirical Formulamentioning
confidence: 99%
See 3 more Smart Citations